State-commercial farmers’ relations in post-colonial Zimbabwe: from willing-seller-willing-buyer dispensation to the new dispensation (1980-2018) - Chibanda, Tawanda W. (Midlands State University, 2021)
The aim of this study was to interrogate state-farmer relations in independent Zimbabwe. It specifically unpacks how farmer unions negotiated and bargained with the post-colonial government for better access to market, finance, extension services and favourable land ownership regimes. It is a qualitative study which draws data from document analysis and oral interviews. The specific focus of this study is to analyse relations between the state and commercial farmers from the willing-seller-willing-buyer dispensation to the new dispensation. The study mainly focuses on commercial farmers’ lobbying and advocacy and the various strategies they developed in engaging the government to enhance commercial farming endeavours in Zimbabwe. By focusing on the relations between the state and commercial farmers organisations the study seeks to shift the angle of analysis from the conventional narratives on agriculture in Zimbabwe that largely focus on land distribution politics. The central argument presented is that state-commercial farmers’ relations witnessed revisions and changes as a result of the emotive politics of land distribution. In terms of the aims, the study interrogates how the Commercial Farmers Union interacted with the state, it also examines the fragmentation of the Commercial Farmers Union leading to the birth of splinter unions such as Justice for Agriculture. The study analyses how reactionary entities such as JAG worked with the state. The study also examines the relationship between the state and black commercial farmers unions such as the Indigenous Commercial Farmers Union and the Zimbabwe Farmers Union. The study unpacks how the state has supported black farmers.The study deploys the theory of corporatism in explaining the relationship between the state and white farmers operating under the Commercial Farmers Union ambit. De-coloniality is used in analysing the relationship between the state and black farmer organisations such as Zimbabwe Farmers Union and Indigenous Commercial Farmers Union. In terms of contribution to knowledge, the study adds black farmer unions to the matrix of state-farmer relations given that previous works largely focused on analysing relations between the state and the white dominated CFU. The study also interrogates the current dispensation of white farmer compensation and analyses how it impacts on state-farmer relations. Finally, the thesis makes a strong case that the unresolved land question is central in understanding state-commercial farmers’ relations in post-colonial Zimbabwe.